Dissolved effluent organic matter: Characteristics and potential implications in wastewater treatment and reuse applications. (15th June 2015) - Michael-Kordatou, I.; Michael, C.; Duan, X.; He, X.; Dionysiou, D.D.; Mills, M.A.; Fatta-Kassinos, D.
Abstract: Wastewater reuse is currently considered globally as the most critical element of sustainable water management. The dissolved effluent organic matter (dEf OM) present in biologically treated urban wastewater, consists of a heterogeneous mixture of refractory organic compounds with diverse structures and varying origin, including dissolved natural organic matter, soluble microbial products, endocrine disrupting compounds, pharmaceuticals and personal care products residues, disinfection by-products, metabolites/transformation products and others, which can reach the aquatic environment through discharge and reuse applications. dEf OM constitutes the major fraction of the effluent organic matter (Ef OM) and due to its chemical complexity, it is necessary to utilize a battery of complementary techniques to adequately describe its structural and functional character. dEf OM has been shown to exhibit contrasting effects towards various aquatic organisms. It decreases metal uptake, thus potentially reducing their bioavailability to exposed organisms. On the other hand, dEf OM can be adsorbed on cell membranes inducing toxic effects. This review paper evaluates the performance of various advanced treatment processes (i.e., membrane filtration and separation processes, activated carbon adsorption, ion-exchange resin process, and advanced chemical oxidation processes) in removing dEf OM from wastewater effluents. In general, the literature findings reveal that dEf OM removal by advanced treatment processes depends on the type and the amount of organic compounds present in the aqueous matrix, as well as the operational parameters and the removal mechanisms taking place during the application of each treatment technology. Graphical abstract: Highlights: Effects and challenges associated with dEf OM and wastewater reuse are discussed. The efficiency of advanced treatment in removing dEf OM is assessed. dEf OM can reduce metal bioavailability or can induce toxicity to microorganisms. SMPs are mainly responsible for membrane fouling and formation of DBPs. UV-driven AOPs are an attractive option to minimize dEf OM.